2017
DOI: 10.12688/f1000research.10870.1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical education and adult learning: Integrating theory into practice

Abstract: Surgical education continues to evolve from the master-apprentice model. Newer methods of the process need to be used to manage the dual challenges of educating while providing safe surgical care. This requires integrating adult learning concepts into delivery of practical training and education in busy clinical environments. A narrative review aimed at outlining and integrating adult learning and surgical education theory was undertaken. Additionally, this information was used to relate the practical delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 36 publications
0
14
0
8
Order By: Relevance
“…Learning theories permit the interpretation of the outcomes of interventions and allows these to be applied in different situations 62 . They also summarize and bring to light the values, attitudes and cultural teaching that are observed from individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…Learning theories permit the interpretation of the outcomes of interventions and allows these to be applied in different situations 62 . They also summarize and bring to light the values, attitudes and cultural teaching that are observed from individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…A narrative review of surgical education and adult learning has identified numerous themes, including the importance of patience and tolerance. 15 …”
Section: Discussionmentioning
confidence: 99%
“…To conduct group discussions, the participants were divided into two groups, one with 22 participants and the other with 21, with each group guided by 1–2 dentists and experts in health education (researcher). Adult learning theory states that adults learn from their past experiences [34], and in group discussion methods, individuals can equally participate and share their experiences, hence the fact that this method of training was selected and implemented.…”
Section: Group Discussionmentioning
confidence: 99%